Exploration of Digital Literacy Among Muslim Household Women in West Bengal, India - Deblina Talukdar; Jayanta Mete (UIN Sunan Gunung Djati Bandung, 2022)
Digital literacy is the ability of an individual to locate, organize, evaluate, analyze and use the required information using digital technologies. It includes a working knowledge of several technologies and understanding of how it can be used. The main objective of the study was to explore the digital literacy of the Muslim household women from West Bengal. The present study also determines the type of device used by them, determining the usage purpose and examines the digital literacy skill.The study is Descriptive survey nature where purposive sampling techniques has been adopted for selecting the respondents from the study area of West Bengal. The total number of respondents were 103. As a research instrument investigator used two different tools- firstly Self-made questionnaire on the usage purpose. Secondly, Digital skill questionnaire developed by "Clinically validated Integrated Support for Assistive Care and Lifestyle Improvement: the Human Link -Vinci". The data were analyzed with the help of descriptive and inferential statistics using SPSS software.The findings of the study reveals that there is significant relationship between the usage purpose of internet and the digital literacy.The highly significant relationship is found between involving in social networking sites for communication i.e., .937, which indicates that due to rapid increase of internet use through digital gadgets for communicating with different social networking sites has gradually empowered their digital literacy.The cause and effect level is high and the null hypothesis is rejected. Here digital skill is influenced by the factors of competency level, communication level, content creation level, ability to adopt safety measures and communication level.Therefore now days household women while maintaining the home tradition and culture parallel they are also maintaining track with the digital world as because some of them may have pre- literacy digital skill before their marriage or they may have learned after their marriage.